2019
DOI: 10.1101/805309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broad binaural fusion impairs segregation of speech based on voice pitch differences in a ‘cocktail party’ environment

Abstract: words)In the normal auditory system, central auditory neurons are sharply tuned to the same frequency ranges for each ear. This precise tuning is mirrored behaviorally as the binaural fusion of tones evoking similar pitches across ears. In contrast, hearing-impaired listeners exhibit abnormally broad tuning of binaural pitch fusion, fusing sounds with pitches differing by up to 3-4 octaves across ears into a single object. Here we present evidence that such broad fusion may similarly impair the segregation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Results from listeners HI25, HI38, and HI40 were based on the average of two different fusion range estimates where the left and right ear were each used as the reference ear, while all others only used one reference ear and fusion function. The results indicate that fusion ranges tended to be larger for listeners with HI compared to NH, as in previous experiments with listeners who use bilateral hearing aids (Oh et al, 2019;Reiss et al, 2017Reiss et al, , 2016. Only 4/9 of the HI data points indicate fusion ranges at or below the greatest NH fusion range.…”
Section: Fusion Rangesupporting
confidence: 72%
See 2 more Smart Citations
“…Results from listeners HI25, HI38, and HI40 were based on the average of two different fusion range estimates where the left and right ear were each used as the reference ear, while all others only used one reference ear and fusion function. The results indicate that fusion ranges tended to be larger for listeners with HI compared to NH, as in previous experiments with listeners who use bilateral hearing aids (Oh et al, 2019;Reiss et al, 2017Reiss et al, , 2016. Only 4/9 of the HI data points indicate fusion ranges at or below the greatest NH fusion range.…”
Section: Fusion Rangesupporting
confidence: 72%
“…The present experiment investigated whether sound level affected the interaural frequency disparity over which two pure tones are heard as one pitch (fusion range). It was hypothesized that if increased sound level contributes to the larger fusion ranges observed in previous studies in listeners with HI who use hearing aids compared to NH (Oh et al, 2019;Reiss et al, 2017Reiss et al, , 2016, then fusion range would also increase for higher sound levels in listeners with NH. The results of the present experiment contradict this hypothesis and suggest that increases in sound level alone do not lead to consistent increases in fusion range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studying this further may lead to another path for intervention to help with the rehabilitative care of hearing-impaired listeners. As proposed by Oh et al (2019) , abnormally broad binaural fusion which is often observed in hearing-impaired listeners could interfere with the segregation of auditory objects based on pitch differences, such as multiple voices in a multi-talker listening environment. Increased understanding of abnormal binaural fusion in hearing-impaired listeners can provide information for future design and training with device-based rehabilitative strategies to enhance the benefits of binaural processing for speech perception in noise.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study by Oh et al (2019) suggested that broad fusion is associated with greater difficulty in using voice pitch difference cues to separate a target voice from other interfering voices in both NH and HI listeners. In other words, the broader the pitch fusion, the smaller the benefit from voice pitch differences because broad fusion could lead to abnormal spectral fusion and blending of words from voices of different pitches.…”
Section: Introductionmentioning
confidence: 99%